A closer look inside nanotubes: Pore structure evaluation of anodized alumina templated carbon nanotube membranes through adsorption and permeability studies - Pilatos, G.; Vermisoglou, E.C.; Romanos, G.E.; Karanikolos, G.N.; N. Boukos; V. Likodimos; Kanellopoulos, N.K. (Advanced Functional Materials, 2010)
Although hollow nanostructures, such as nanotubes, represent a major portion of nanoscaled materials with a tremendously large application range, a detailed evaluation of their internal characteristics still remains elusive. Transmission electron microscopy is the most common analytical technique to examine the internal configuration of these structures, yet it can only provide evidence of a minimal portion of the overall material, thus, it cannot be accurately generalized. In the present paper, in addition to electron microscopy and other spot-size analysis methods (X-ray diffraction, Raman spectroscopy, etc.), a combination of techniques including adsorption, permeability, and relative permeability are employed in order to provide important insights into various crucial details of the overall internal surface and hollow-space characteristics of carbon nanotube (CNT) arrays and membranes. The CNT arrays are fabricated using anodized alumina as a template in a flow-through chemical vapor deposition (CVD) reactor. This is the first systematic approach for investigating the internal configuration of template-based CNT arrays in detail. Key findings are made fiar the customized optimization of the resulting nanotube membranes for a variety of applications, including separations, nanofluidics and nanoreactors, biological capturing and purification, and controlled drug delivery and release. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhelm.